Geotechnical and geological investigation of landslide in western GHAT of Maharashtra, India - J. Khamkar, Dattatraya; Y. Mha, Sumedh; D. Sabale, Pandurang (International Journal of Engineering and Technology, 2018)
The problem of the landslide is severe in Western ghat of Maharashtra mostly due to the topography, human interference, heavy rainfall etc. Upland region of Deccan Volcanic Provinces (DVP) is considered as a most vulnerable region for landslides activity in the Maharashtra state of India. The area shows thick flows of the Deccan Trap basalt of Upper Cretaceous to Eocene age. State Highway -70 is the lifeline of the Pune District and Raigarh District of Konkan. The part of the highway between Bhor and Mahad is highly landslide prone and frequently blocked during the rainy season. Considering the importance of SH-70, landslide susceptibility zonation studies along SH-70 between Bhor and Mahad were carried out. The landslide susceptibility study gives an overall idea of the stability condition of the slopes of the hill so it can be used for planning any further construction activity and remedial measures. A detailed exploration was carried out along the road section started from Bhor city, and it extended up to the Mahad, in Konkan region. Paper discusses the geological, geotechnical investigation of the area. The remedial measures are suggested to minimize the severity of landslide.Â Â